Determinants of Malaria Morbidity Among School-Aged Children Living in East Hararghe Zone, Oromia, Ethiopia: A Community-Based Case–Control Study - Abdishu M; Gobena T; Damena M; Abdi H; Birhanu A (Dove Medical Press, 2022)
Mohammedawel Abdishu,1 Tesfaye Gobena,2 Melake Damena,2 Hassen Abdi,2 Abdi Birhanu3 1Public Health Emergency Management Officer at Gursum District Health Office, Gursum, Oromia Region, Ethiopia; 2Haramaya University, College of Health and Medical Sciences, School of Public Health, Harar, Ethiopia; 3Haramaya University, College of Health and Medical Sciences, School of Medicine, Harar, EthiopiaCorrespondence: Abdi Birhanu, Email abdiibiree@gmail.comBackground: Understanding the determinants of malaria morbidity offers helpful insights toward the changing malaria situation, which might lead to the adjustment of malaria program activities. Even though the determinants of malaria morbidity remain unknown, school-aged children were the highest malaria morbidity contributors in the East Hararghe Zone. Therefore, this study aimed to assess the determinants of malaria morbidity among school-aged children in the study area from February 1 to May 31, 2020.Methods: A case-control study was conducted among school-aged children living in ten randomly selected low, moderate, and high malaria transmission kebeles. Cases were confirmed as positive for malaria, while controls were confirmed as negative for malaria among randomly selected school-aged children. Rapid diagnostic testing (RDT) and blood film (BF) malaria testing methods were used. Multivariable logistic regression was used to identify association between malaria and its determinants.Results: The determinants of malaria infection were having no formal education (adjusted odds ratio (AOR)=4.91, 95% CI: 1.20- 20.17), low family wealth index (AOR=2.50, 95% CI: 1.22- 5.12), being from rural residence (AOR=2.34, 95% CI: 1.87- 4.12), living near to stagnant water (AOR=2.01, 95% CI: 1.14- 3.54), having a maximum of three family members (AOR=0.37, 95% CI: 0.18- 0.78), using indoor residual spraying (IRS) (AOR=0.15, 95% CI: 0.08- 0.29) and long-lasting insecticide-treated net (LLITN) over the last night (AOR=0.19, 95% CI: 0.10- 0.35), and living in the house surrounded by cultivated land(AOR=0.24, 95%CI: 0.10-0.60) compared with their counterparts.Conclusion: This study revealed that residence, family size, education, wealth index, stagnant water existence, and using LLITN and IRS had significant association with malaria morbidity. Thus, all concerned bodies, including the community should strengthen working on stagnant water elimination around their house to cut the breeding site of the malaria vector mosquito. Moreover, the findings have an important implication for improving interventions targeting the economic status and literacy of the society that may help in the reduction of the risk of malaria in the school-aged children.Keywords: determinants, malaria, school-aged children, Ethiopia